An overview on hermeneutics method application to the Quran by Muslim thinkers - Zainol, Nur Zainatul Nadra; Abdul Majid, Latifah; Md Saad, Mohd Faizulamri (Science Publishing Corporation, 2018)
Hermeneutics method was introduced by modern Islamic thinkers where they see the need to apply the methods of hermeneutics in the interpretation of the Quran. Among of the thinkers are Fazlur Rahman, Nasr Hamid Abu Zayd and Arkoun who applying hermeneutics. Thus it occur a debate among Muslim scholars. Hence, this study aims to analyse the methods introduced by these scholars which were emphasizing in hermeneutics aspects.In this paper, the method of content analysis conducted can gatherrelevant facts on hermeneutics methods that have been applied against the Quran by modern thinkers as well as collecting information in other forms of interpretation that have been conducted by these modern thinkers. The views of contemporary scholars onthe true interpretation of Quran was also identified to argue the opinions of the modern thinkers who justify the hermeneutics methods.this study shows those modern thinkers have used the theories of hermeneutics as literary criticism, history and semiotic study of the Quran. The use of the method has downgraded the Quran by equating the Quran as literary works. Reinterpretationof the verses of the Quran based on the current context has made the issue of fiqh change and become controversial and this is against the opinion of the majority of scholars.